A brief history of primordial light from the perspectives of Sufi and modern science - Wan Qashishah Akmal Wan Razali,; Ahmad Fakhrurrazi Mohammed Zabidi,; Shahidan Radiman,; Abdul Latif Samian, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The primordial light is fundamental in the creation of the universe from the Sufi cosmology. In particular of the Sufi tradition, the Ishrāqἱ (illumination) school serves as a major School of thought in the Islamic intellectual history with the knowledge of the Muhammadan Light (Nūr Muhammad) becoming the most prominent cosmological point of debate among of Muslim scholars. To date, discussions and reviews on the understanding of the Muhammadan Light from the perspective of theology, literature, philosophy and the cosmological view in comparison to modern cosmology are still lacking. In modern cosmology, the Big Bang theory which is directly related to the light cosmology has been significantly discussed. The present study provides additional evidence with respect to the cosmological perspective highlighting the importance of light cosmology aspects with the insights of combining both cosmological postulates by evidence of direct connection with current modern and Sufi cosmology (worldviews). The present study renders the understanding of the gnosis of God and His Prophet Muhammad PBUH through the light cosmology perspective.